Communication And Language Use Analysis By Gender Pattern Between Mr. And Mrs. Smith” Movie - Nanan Kandagasari; Mutiara Indah Nirmala Dewi; Muhammad Lutfi Wiguna (Journal on Education, 2023)
This research is entitled “Communication and Language Use Analysis by Gender Pattern Between “Mr. and Mrs. Smith” Movie. The objectives of this study are to know the types of language differences between men and women found in the movie “Mr. and Mrs. Smith”, and to describe how language differences represent gender differences. This research was qualitative descriptive research. The source of data was the printed transcript of the movie “Mr. and Mrs. Smith”. The theories used in this thesis are theories proposed by Lakoff (2004). The result of the research found that the types of language differences represent gender differences. The types of language differences describing gender differences include vocabulary, syntax, and choosing topics. From the ten tracts which are taken to be the data on this study, the researcher found that most women’s expressions are made up of adjectives and adverbs represented in characters’ dialogues along the movie. Meanwhile, when choosing the topics, women and men have different things such as language, activity, and emotion, etc. It is very different to compare between women and men.